1983
DOI: 10.2307/1937829
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of Soft‐Bottom Benthic Succession By Tube Builders

Abstract: Controlled field experiments were used to test the effects of surface—deposit feeders on succession at the Skagit flats, an intertidal sandflat in northern Puget Sound. The tube builders Hobsonia florida (Polychaeta, Ampharetidae), Pseudopolydora kempi japonica (Polychaeta, Spionidae), and Lanais sp. (Crustacea, Peracarida) facilitate the recruitment of other taxa on 10—cm2 azoic patches. Simulated animal tubes facilitated the immigration of Tanais sp. and oligochaetes. Macoma balthica, a tellinid bivalve, fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
2
2

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(121 citation statements)
references
References 44 publications
6
111
2
2
Order By: Relevance
“…size-dependent predation or flow-mediated effects often characteristic of adult-larval interactions (e.g. Eckman 1983;Gallagher et al 1983;Oliver and Slattery 1985b). Such adult-adult interactions should be explicitly considered in successional models for the muddy seafloor, in contrast to models of communities (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…size-dependent predation or flow-mediated effects often characteristic of adult-larval interactions (e.g. Eckman 1983;Gallagher et al 1983;Oliver and Slattery 1985b). Such adult-adult interactions should be explicitly considered in successional models for the muddy seafloor, in contrast to models of communities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, succession edge of any dependence of colonization prowithin a recently disturbed patch, i.e. temcesses on small-scale variations in patch size poral changes in the identities and proporor substrate isolation would allow more tions of species (sensu Gallagher et al 1983; critical evaluation of this data base, potenDean and Connell 1987), may depend on tially endbling more realistic modeling of the arrival mode of colonists.…”
mentioning
confidence: 99%
“…Although results from the present study indicate that the proportion of background densities attained in unenriched sediment in this study is higher than previously estimated for the deep sea, the rate of colonization was still considerably slower than in shallow-water studies conducted over a similar interval. For example, Gallagher et al (1983) used flush, hydrodynamically unbiased trays to evaluate shallow-water colonization and found that even without enrichment, colonization densities actually exceeded ambient densities.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…However, Weinberg (1984) showed that another tube-dwelling spionid polychaete, Polydora ligni, does consume G. gemma juveniles and reduces adult survival. On the other hand, tube-dwelling species have been shown experimentally to facilitate the recruitment of other species in soft-bottom communities (Gallagher et al 1983).…”
Section: Species Interactionsmentioning
confidence: 99%